Uplink design in VLC systems with IR sources and beam steering. Issue 3 (1st February 2017) - Alresheedi, Mohammed T.; Hussein, Ahmed Taha; Elmirghani, Jaafar M.H.
Abstract : The need for high‐speed local area networks to meet the recent developments in multimedia and video transmission applications has recently focused interest on visible light communication (VLC) systems. Although VLC systems provide lighting and communications simultaneously from light emitting diodes (LEDs), LEDs, the uplink channel design in such a system is a challenging task. In this study, the authors propose a solution in which the uplink challenge in indoor VLC is resolved by the use of an infrared (IR) link. The authors introduce a novel fast adaptive beam steering IR system (FABS‐IR) to improve the uplink performance at high data rates while providing security for applications. The goal of the authors' proposed system is to enhance the received optical power signal, speed up the adaptation process and mitigate the channel delay spread when the system operates at a high transmission rate. The channel delay spread is minimised from 0.22 ns given by hybrid diffuse IR link to almost 0.07 ns. At 2.5 Gb/s, the authors' results show that the imaging FABS‐IR system accomplished about 11.7 dB signal to noise ratio in the presence of multipath dispersion, receiver noise and transmitter mobility.